Revising the Integration-Citizenship Nexus in Europe Sites, Policies, and Bureaucracies of Belonging - Barbulescu, Roxana; Goodman, Sara Wallace; Pedroza, Luicy (IMISCOE Research Series,, 2023)
This open access book critically re-examines the theoretical and empirical interconnections between integration and citizenship, specifically, naturalisation. With new, empirical-grounded analyses of what we term the "life of citizenship," the central, shared contribution is showcasing how membership is informally achieved through everyday integration -usually around, but sometimes in spite of, formal citizenship requirements. By providing evidence of a nexus disjuncture, the book contributes to critical dialogues on immigrant integration and political incorporation, relevant for policymakers, civil society actors, and academics alike.